Income inequality, tourism and resources endowment in Uruguay: a spatial and distributional approach - Porto, Natalia (2020)
It has been widely recognized that tourism plays a crucial role both as an income generator and as a source of employment, thus contributing to economic growth and development of many countries around the world. While its impact at local, regional and national level of employment is undoubted and has been broadly documented, there is a line of research that has pointed out that jobs in tourism sector have less favorable working conditions than other sectors and, also, they could have negative effects on income distribution. Another interesting feature that could be also related to income distribution is the regional endowment of touristic amenities. Both natural and built amenities directly affect tourism activities, thus having a strong impact on income generation of tourism. Considering these two facts, it is possible that the allocation and distribution of amenities in a country could generate regional disparities in income distribution due to tourism. The aim of this study is to explore regional inequalities in wages and its relationship with the development of tourism in Uruguay. We estimate a spatial error model using a balanced panel data set from 2006 to 2019 on 19 Uruguayan departments. We built four indices of touristic amenities (land-based natural amenities, water-based natural amenities, culturalhistorical amenities, and recreational amenities) and then interact them with tourism employment, as a proxy for tourism development. The evidence suggests that there are some regional disparities in income distribution in tourism sector. Also, some specifications of the econometric models show a positive relationship between employment in activities related to tourism and inequality in labor income, and that the departments with cultural-historical amenities tend to have a more equalitarian distribution of labor income.